The Christian education of children and youth - Miller, Samuel (Presbyterian Board of Publication, 1840)
Report to the General Assembly, on Christian education. By the Rev. S. Miller. -- Report to the Synod of New Jersey on the subject of parochial schools. By the Rev. J.J. Janeway.